Environmental study of natural radioactivity regime of the Ikaria island and the radiological impact - Trabidou, G.; Florou, H.; Angelopoulos, A.; Sakelliou, L.; Katsikis, I. (HNPS Advances in Nuclear Physics, 2020)
This is a preliminary study on the natural radioactivity of the spas in the Icaria island and the consequent impact to the public health. In order to carry out this research : a) Car-borne radiometry has been applied in the areas around the spas as well as in some reference areas in the island b) The activity concentrations of the natural radionuclides of the 238U-226Ra and 232Th decay series, as well as 40K, in spa water, soil, sediment, surface sea water and marine flora samples in the areas of the spas were measured, from the results derived one notes that elevated concentrations of the environmental abiotic materials are presented, which are reflected to the concentrations observed in marine flora. Consequently, higher population doses in comparison with other Greek regions are resulted.